Respuestas

2013-11-14T22:39:04+01:00
1/3  x   + ( 4x-1)/x/6= (x+2/x)/3-1/6

x       +  ( 4x- 1 ) 6       ( x+2 ) 6        
-----        --------------   =  ---------------    
 3               x                  x  . 17          

x/3  + (24x -6) /x  = (6x + 12 ) / 17 x

(x^2  +  18 ( 4x -1)) / 3x  = 
(6x + 12 ) / 17 x

(x^2 + 72 x -18 ) . 17 x = ( 6x + 12 ) . 3x

17 x^3 + 1224 x^2 - 306 x  = 18 x^2 + 36 x 

17x^3 +1206 x^2 -342 x = 0

17x^2 + 1206 x -342 = 0


-1206±√1206²+4. 342. 17
--------------------------------------   =  1206 +1215 /34 = 71                     
      2 . 17